Effectiveness of an array of porous fences to reduce sand flux: Oceano Dunes, Oceano CA. Issue 168 (September 2017) - Gillies, J.A.; Etyemezian, V.; Nikolich, G.; Glick, R.; Rowland, P.; Pesce, T.; Skinner, M.
Abstract: Arrays of porous fences, ≈12 ha in 2014 and ≈ 15 ha in 2015, were constructed in the Oceano Dunes State Vehicular Recreation Area to evaluate their effectiveness to reduce sand flux and affect local PM10 dust concentrations. The 1.22 m high, ≥244 m long, ≈50% porous fences were placed 10 fence heights apart in 2014 and 7 in 2015. Measurements of sand flux through the arrays indicated that it diminished exponentially with increasing distance, reaching equilibrium at ≈93 fence heights for the 10 h spacing and ≈27 fence heights for the 7 h spacing. Fences spaced 7 h apart reduced sand flux for the entire area by 78%, and 86% for the area ≥27 h. Fences spaced at 10 h reduced sand flux for the entire area by 40%, and 56% for the area ≥93 h. PM10 monitoring upwind and downwind of the array and in the absence of the array in 2015, indicated that the downwind PM10 concentration was less than the upwind for the fence array, whereas in the absence of fences PM10 increased in the downwind direction over the same fetch distance, suggesting the presence of the fences was reducing the flux of PM10 from within the fence array. Highlights: The effectiveness of multiple porous fence arrays to reduce sand flux and local PM10 concentrations was evaluated. Effectiveness to reduce sand flux scales with inter-row spacing. Sand flux decreases exponentially with horizontal distance and the rate of reduction is a function of fence spacing. Porous fences decrease sand flux at a faster rate with into the array than an array of solid elements designed to achieve the same level of control. The PM10 concentration at the downwind edge of the array was less than the upwind, suggesting flux of PM10 from the sand was reduced.